2010
DOI: 10.1016/j.amjsurg.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasonography and mammography in predicting pathologic response after neoadjuvant chemotherapy for breast cancer

Abstract: BACKGROUND Neoadjuvant chemotherapy reduces tumor size prior to surgery in women with breast cancer. We assessed the ability of mammography and ultrasound to predict residual tumor size following neoadjuvant chemotherapy. METHODS In a retrospective review of consecutive breast cancer patients treated with neoadjuvant chemotherapy, residual tumor size estimated by diagnostic imaging was compared with residual tumor size determined by surgical pathology. RESULTS 192 patients with 196 primary breast cancers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 50 publications
6
57
1
2
Order By: Relevance
“…The accuracy of MG in measuring the residual tumour to within 1 cm of the histopathological size was 60.0% in our study, which is similar to that calculated by Atkins et al 14 (56.0%) but higher than that found by Keune et al 15 (31.7%) and lower than that found by Chagpar et al 16 (70.0%).…”
Section: Discussionsupporting
confidence: 88%
“…The accuracy of MG in measuring the residual tumour to within 1 cm of the histopathological size was 60.0% in our study, which is similar to that calculated by Atkins et al 14 (56.0%) but higher than that found by Keune et al 15 (31.7%) and lower than that found by Chagpar et al 16 (70.0%).…”
Section: Discussionsupporting
confidence: 88%
“…However, studies comparatively analyzing the diagnostic accuracy of MMG and sonography demonstrated that the two modalities perform equally well in detecting primary breast cancer (11,17), or that MMG is superior to breast US in the accurate diagnosis of primary breast cancer (2,18). Although it has been reported that US was more accurate compared with MMG in predicting residual tumor size following neoadjuvant chemotherapy (19), there is no available literature regarding the optimal method for accurate assessment of residual disease following bioptic lumpectomy. Identifying residual tumor following lumpectomy may be even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mammography and ultrasonography for measuring residual tumor size after neoadjuvant chemotherapy has been reported previously [23,24]. Keune et al [25] recently compared the accuracy of mammography and ultrasonography in predicting pathologic response after neoadjuvant chemotherapy. Breast ultrasound was more accurate than mammography; ultrasound was able to size the final disease in 91.3% compared to only 51.9% when mammography was used ( < 0.001).…”
Section: Discussionmentioning
confidence: 99%